Evaluasi Potensi Lahan untuk Pengembangan Beberapa Jenis Tanaman Hortikultura Berbasis SIG (Sistem Informasi Geografis) pada Subak di Kecamatan Denpasar Utara Kota Denpasar Provinsi Bali - Hutauruk, Josua Sintong Martin; Trigunasih, Ni Made; Dibia, I Nyoman (Nandur; Vol 1 No 2 (2021), 2021)
This study aims to determine the actual and potential land suitability, limiting factors, provide land use direction and create a land suitability map for horticultural crops in North Denpasar District. This study uses field survey methods, soil analysis at the Laboratory of Soil and Environmental Sciences, Faculty of Agriculture, Udayana University, and the matching method. Observation of sample points was carried out by purposive sampling in each subak. Sampling was carried out to a depth of 30 cm. The results showed that the actual land suitability class for horticultural crops (sweet potato, potato, chili, tomato and eggplant) was classified as S3 (marginally appropriate) to N (not suitable) with the limiting factors being temperature, rainfall, N-total, K2O, and erosion hazard. Improvement efforts can be made by giving organic matter, giving Urea and KCl fertilizer. Potential land suitability classes for horticultural crops are classified as S3 (marginal appropriate) to N (not suitable), with temperature and rainfall limiting factors. The types of plants recommended for Subak Dalem, Kedua, Lungatad, Pakel II, Petangan, Ubung, and Sembung are sweet potatoes, chilies, tomatoes, and eggplants. The types of plants recommended for subak Pakel I are chili, tomato, and eggplant.